Prenatal diagnosis and outcome of fetuses with isolated agenesis of septum pellucidum: cohort study and meta‐analysis. (18th January 2022) - Di Pasquo, E.; Kuleva, M.; Arthuis, C.; Morganelli, G.; Ormitti, F.; Millischer, A.‐E.; Grevent, D.; Ville, Y.; Ghi, T.; Salomon, L. J.
ABSTRACT: Objective: To evaluate the postnatal outcome of children with a prenatal diagnosis of apparently isolated agenesis of the septum pellucidum (ASP). Methods: A retrospective cohort study of cases of prenatally diagnosed ASP followed in two tertiary centers and a meta‐analysis combining data from the cohort study with data from published studies identified in a systematic review were carried out. Only cases with apparently isolated ASP on antenatal ultrasound and/or magnetic resonance imaging and with available postnatal follow‐up data were considered eligible for inclusion. The following outcomes were analyzed: incidence of chromosomal anomalies, agreement between antenatal and postnatal findings, overall incidence of septo‐optic dysplasia (SOD) and incidence of major neurological disability (motor, language, coordination or behavioral disorder or epilepsy) in non‐SOD children. The incidence of SOD in infants with apparently normal optic pathways on antenatal imaging was also evaluated. Results: Fifteen cases of isolated ASP, with median postnatal follow‐up of 36 months (range, 12–60 months), were selected from the two centers. Six previously published studies met the inclusion criteria for the systematic review and a total of 78 cases were eligible for the analysis, including the 15 cases from our series. Genetic tests were carried out antenatally in 30 fetuses, of which two had an abnormal result (pooled proportion, 9.0% (95% CI, 1.8–20.7%); I 2  = 0%). Additional or discordant imaging findings were noted postnatally in 9/70 (pooled proportion, 13.7% (95% CI, 3.5–29.0%); I 2  = 63.9%) cases. Of all 78 neonates with available follow‐up, SOD was diagnosed postnatally in 14 (pooled proportion, 19.4% (95% CI, 8.6–33.2%); I 2  = 51.2%). In 60 cases, the optic pathways were considered to be normal on antenatal imaging, and six of these (pooled proportion, 9.1% (95% CI, 1.1–24.0%); I 2  = 62.0%) were diagnosed postnatally with SOD. Of the 46 infants with available neurological follow‐up who were not affected by SOD, a major neurological disability was diagnosed in three (pooled proportion, 6.5% (95% CI, 0.5–18.6%); I 2  = 40.1%). Conclusions: In the vast majority of cases with a prenatal diagnosis of apparently isolated ASP, the prognosis is favorable. However, an additional anomaly is detected after birth in about 14% of cases and has a negative impact on clinical outcome. Detailed antenatal assessment of the brain and optic pathways is strongly recommended in order to identify the presence of associated anomalies. Antenatal visualization of apparently normal optic pathways does not rule out SOD. © 2021 International Society of Ultrasound in Obstetrics and Gynecology. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Diagnóstico prenatal y resultado de los fetos con agenesia aislada del septum pellucidum : estudio de cohortes y metaanálisis Objetivo: Evaluar el resultado postnatal de los niños con un diagnóstico prenatal de agenesia del septum pellucidum (ASP) aparentemente aislada. Métodos: Se realizó un estudio de cohorte retrospectivo de casos de ASP diagnosticados prenatalmente y a los que se dio seguimiento en dos centros terciarios y un metaanálisis que combinó los datos del estudio de cohorte con los datos de los estudios publicados identificados en una revisión sistemática. Sólo se consideraron elegibles para su inclusión los casos con una ASP aparentemente aislada en la ecografía prenatal y/o la resonancia magnética y con datos de seguimiento postnatal disponibles. Se analizaron los siguientes resultados: incidencia de anomalías cromosómicas, concordancia entre los hallazgos prenatales y postnatales, incidencia general de displasia septo‐óptica (DSO) e incidencia de discapacidad neurológica grave (trastorno motor, del lenguaje, de la coordinación o del comportamiento o epilepsia) en niños sin DSO. También se evaluó la incidencia de DSO en bebés con vías ópticas aparentemente normales en las imágenes prenatales. Resultados: Se seleccionaron 15 casos de ASP aislada, con una mediana de seguimiento postnatal de 36 meses (rango, 12–60 meses), procedentes de los dos centros. Seis estudios publicados previamente cumplieron los criterios de inclusión para la revisión sistemática y un total de 78 casos fueron elegibles para el análisis, entre ellos los 15 casos seleccionados. Se realizaron pruebas genéticas prenatales en 30 fetos, de los cuales dos tuvieron un resultado anómalo (proporción agrupada, 9, 0% (IC 95%, 1, 8–20, 7%); I2 =0%). Se observaron hallazgos adicionales o discordantes en las imágenes en el periodo postnatal en 9 de 70 casos (proporción agrupada, 13, 7% (IC 95%, 3, 5–29, 0%); I2 =63, 9%). De los 78 recién nacidos con seguimiento disponible, el DSO se diagnosticó postnatalmente en 14 (proporción agrupada, 19, 4% (IC 95%, 8, 6–33, 2%); I2 =51, 2%). En 60 casos, las vías ópticas se consideraron normales en las imágenes prenatales, y en seis de ellos (proporción agrupada, 9, 1% (IC 95%, 1, 1–24, 0%); I2 =62, 0%) se diagnosticó postnatalmente DSO. De los 46 bebés con seguimiento neurológico disponible que no estaban afectados por la DSO, se diagnosticó una discapacidad neurológica grave en tres de ellos (proporción agrupada, 6, 5% (IC 95%, 0, 5–18, 6%); I2 =40, 1%). Conclusiones: En la gran mayoría de los casos con diagnóstico prenatal de ASP aparentemente aislado, el pronóstico es favorable. Sin embargo, se detecta una anomalía adicional después del nacimiento en aproximadamente el 14% de los casos y tiene un impacto negativo en el resultado clínico. Se recomienda encarecidamente una evaluación prenatal detallada del cerebro y las vías ópticas para identificar la presencia de anomalías asociadas. La visualización prenatal de las vías ópticas aparentemente normales no descarta la DSO. © 2021 International Society of Ultrasound in Obstetrics and Gynecology. 摘要: 单纯性透明隔缺如胎儿的产前诊断及结果:人群队列研究和荟萃分析 目的: 评估产前诊断为明显单纯性透明隔缺如(ASP)儿童的产后结果。 方法: 在两家第三级中心跟踪产前诊断为ASP的病例而进行的一项回顾性队列研究，结合人群队列研究的数据和一次系统评价中确定的已发表文献的数据展开荟萃分析。 仅包含在产前超声和/或磁共振成像中明显为单纯性ASP并有产后随访数据的病例。分析了以下结果:染色体异常的发病率、产前及产后检查发现情况的一致性，视‐隔发育不良(SOD)的总发病率，以及在非SOD儿童中主要神经残障(运动、语言、协调能力或行为障碍或癫痫)的发病率。还评估了在产前影像检查中视觉传导通路明显正常婴儿的SOD发病率。 结果: 从两家中心选出15例单纯性ASP，产后随访中位数为36个月(范围:12‐60个月)。六篇已发表研究满足系统评价的纳入标准，总计78个病例符合分析条件，包括我们的15个病例。对30个胎儿进行了产前基因检测，其中两例有异常结果(合并比例，9.0%(95% CI，1.8–20.7%)；I2 =0%)。记录下产后额外或不一致的影像调查结果为9/70例(合并比例，13.7%(95% CI，3.5–29.0%)；I2 =63.9%)。在有可用随访数据的总共78个新生儿中，产后诊断出SOD的有14例(合并比例，19.4%(95% CI，8.6–33.2%)；I2 =51.2%)。在60例中，视路在产前影像时被认为是正常的，其中六例(合并比例，9.1%(95% CI，1.1–24.0%)；I2 =62.0%)在产后诊断出SOD。在有可用神经学随访数据的46个婴儿中(未受SOD的影响)，有三例诊断出主要神经残障(合并比例，6.5%(95% CI，0.5–18.6%)；I2 =40.1%)。 结论: 在绝大多数产前诊断明显为单纯性ASP的病例中，预断病情是有利的。然而，在大约14%的病例中产后发现额外异常，并且对临床结局有不良影响。强烈建议对大脑和视路进行详细的产前评估，以识别相关异常的存在。明显正常视路的产前影像并不排除SOD。© 2021年国际妇产科超声学会。